RANCANG BANGUN TANGAN PALSU UNTUK PENYANDANG DISABILITAS DENGAN MENGGUNAKAN METODE ULRICH - Faris Dawwas; Tri Andi Setiawan; Isa Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Indonesia's diverse population has led to an increasing rate of population growth, resulting in congested activities and various challenges. Among the citizens facing difficulties are those with disabilities, especially physical disabilities. To assist them, both the government and non-governmental organizations provide support, such as creating prosthetic hands, enabling them to engage in daily activities like others. This study utilizes the Ulrich method to design a prosthetic hand, generating multiple design concepts and selecting the fourth one through careful consideration. Using Autodesk Fusion 360 software, stress, strain, and displacement tests were conducted on the chosen design concept. The simulation showed that the ABS plastic used in the prosthetic hand achieved a maximum stress of 0.294 MPa, maximum displacement of 18.76 mm, and maximum strain value of 0.0001693, all falling within a safe blue zone. With the concept established, the next steps included assembling the components, programming the prosthetic hand movements, and conducting final tests.